Disagreeing over evaluatives: preference, normative and moral discourses - Díaz Legaspe, Justina (2015)
Why would we argue about taste, norms or morality when we know that these topics are relative to taste preferences, systems of norms or values to which we are committed? Yet, disagreements over these topics are common in our evaluative discourses. I will claim that the motives to discuss rely on our attitudes towards the standard held by the speakers in each domain of discourse, relating different attitudes to different motives -mainly, conviction and correction. These notions of attitudes and motives will allow me to claim that different domains of evaluative discourse have a different distribution of disagreements driven by them.